67P/Churyumov–Gerasimenko's dust activity from pre- to post-perihelion as detected by Rosetta/GIADA. Issue 1 (30th May 2020) - Longobardo, A; Della Corte, V; Rotundi, A; Fulle, M; Rinaldi, G; Formisano, M; Zakharov, V; Ivanovski, S; Mannel, T; Ciarniello, M; Inno, L; Rubin, M; et al.
ABSTRACT: We characterized the 67P/Churyumov–Gerasimenko's dust activity, by analysing individual dust particle velocity and momentum measurements of Grain Impact Analyser and Dust Accumulator (GIADA), the dust detector onboard the ESA/ Rosetta spacecraft, collecting dust from tens to hundreds of kilometres from the nucleus. Specifically, we developed a procedure to trace back the motion of dust particles down to the nucleus, identifying the surface's region ejecting each dust particle. This procedure has been developed and validated for the first part of the mission by Longobardo et al. and was extended to the entire GIADA data set in this work. The results based on this technique allowed us to investigate the link between the dust porosity (fluffy/compact) and the morphology of the ejecting surface (rough/smooth). We found that fluffy and compact particles, despite the lack of correlation in their coma spatial distribution (at large nucleocentric distances) induced by their different velocities, have common ejection regions. In particular, the correlation between the distributions of fluffy and compact particles is maintained up to an altitude of about 10 km. Fluffy particles are more abundant in rough terrains. This could be the result of past cometary activity that resurfaced the smooth terrains and/or of the comet formation process that stored the fluffy particles inside the voids between the pebbles. The variation of fluffy particle concentration between rough and smooth terrains agrees with predictions of comet formation models. Finally, no correlation between dust distribution on the nucleus and surface thermal properties was found.